Needlestick accident resulting in occupational transmission of HCV: Report of two cases - Chaves, Eunice B Martin; Brum, Maria Carlota Borba; Dantas Filho, Fabio Fernandes; Piana, Marjanai Denti; Stoniasso, Sheila Cardoso; Joveleviths, Dvora (Clinical and Biomedical Research, 2016)
Occupational transmission of hepatitis C virus (HCV) through needlestick injury is a serious problem worldwide. Occupational transmission of HCV is estimated at an average rate between 0,5% and 0,75%. There are factors associated with increased risk of transmission, such as deep injuries, procedures involving hollow-bore needle placement in the source patient’s vein or artery, and high HCV RNA titer in the source patient. We describe two cases of HCV seroconversion in nursing assistants after different risk needlestick injuries. A transmissão ocupacional do vírus da hepatite C (VHC) através de acidentes com material perfurocortante é um problema global. Essa transmissão é estimada, em média, entre 0,5% e 0,75%. Alguns fatores estão associados ao aumento do risco de transmissão, tais como lesões profundas, procedimentos que envolvam colocação da agulha em veia ou artéria, e altos títulos de HCV-RNA no paciente-fonte. Descrevemos dois casos de soroconversão ao VHC em auxiliares de enfermagem após acidentes com agulhas.